Effect of ZnO Nanoparticles on Brassica nigra Seedlings and Stem Explants: Growth Dynamics and Antioxidative Response - Zafar, Hira; Ali, Attarad; Ali, Joham S.; Haq, Ihsan U.; Zia, Muhammad (Frontiers in Plant Science, 2016)
Nanoparticles (NPs) have diverse properties when compared to respective chemicals due to their structure, surface to volume ratio, morphology, and reactivity. Toxicological effects of metallic NPs on organisms including plants have been reported. However, to the best of our knowledge, there is still not any report on the effect of NPs on in vitro culture of plant explants. In this study, ZnO NPs concentration ranging from 500 to 1500 mg/L adversely affects the Brassica nigra seed germination and seedling growth and also lead to an increase in the antioxidative activities and non-enzymatic antioxidants. While, culturing the stem explants of B. nigra on Murashige and Skoog (MS) medium at lower concentration of ZnO NPs (1–20 mg/L) resulted in the production of white thin roots with thick root hairs. At 10 mg/L ZnO NPs, shoots emergence is also observed. The developed calli/roots showed 79% DPPH (2,2-diphenyl-1-picryl hydrazyl) radical scavenging activity at 10 mg/L. The total antioxidant and reducing power potential also significantly affected in presence of ZnO NPs. Moreover, an increase in non-enzymatic antioxidative molecules, phenolics (up to 0.15 μg GAE/mg FW) and flavonoids (up to 0.22 μg QE/mg FW), depending on NPs concentration is also observed. We conclude that ZnO NPs may induce roots from explants cultured on appropriate medium that can be used for production of valuable secondary metabolites.